Intervencija utemeljena na rutinama u ranoj intervenciji kroz grupni rad s obiteljima - Bohaček, Ana-Marija (Array, 2018)
Contemporary approaches to early intervention emphasize the importance of supporting parents and their strong involvement in all forms of intervention. Emphasis has been put on respecting developmental principles that are the same for all children (with or without development difficulties). Children reach developing milestones through interaction with adults and activities (routines) that are part of their natural environment. Because of the specificities of children with developmental disabilities, it is much more demanding for parents to include them in everyday routines, use them and understand them as moments of learning and encouragement. With the aim of providing support to parents in organizing daily routines for promoting socio-communication development, group sessions were organized in which parents were taught strategies for utilizing everyday activities and routines in encouraging child’s development. Five groups of parents (35 parents) of children with suspected or already diagnosed autism spectrum disorders (21 children) have been formed. Each group had 12 structured meetings, after which parents completed the evaluation questionnaire and evaluated the satisfaction with the program they were involved in together with their children. The evaluation questionnaire was highly appreciated by parents, especially regarding communication with experts, content and applicability of the program. In the open-ended part of the questionnaire, parents highly rated the obtained material, as well as the exchange of experiences with other parents. The findings suggest that an intervention approach that supports parents in incorporating developmental goals into everyday routines is a very successful and powerful tool that helps parents encourage a child in various skills. Also, teaching parents new skills together with their children proved to be a very good form of work and it is highly recommended to apply this form more frequently in everyday practice.